2018
DOI: 10.1021/acs.jpcb.8b07499
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Simulation of Strain-Enhanced Stereocomplex Polymer Crystallization

Abstract: We performed dynamic Monte Carlo simulations to investigate strain-induced polymer crystallization under separate enhancements of the driving forces for homocomponent and stereocomplex crystallization in the half–half symmetric racemic polymer blends. The results showed that the polymer strain significantly enhances the stereocomplex crystallization, in comparison to the parallel cases of template-induced crystal growth without any strain in the previous simulations. We attributed the results to the strain-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Molecular simulations have demonstrated that under the same thermodynamic circumstances homocrystals grow faster than stereocomplex crystals, 4 but strain-induced crystallization enhances the preference of primary nucleation of stereocomplex crystals. 5 If the chain lengths are too small to make chain folding, intermolecular crystal nucleation becomes dominant and benefits stereocomplex crystals. 6 In practice, stereocomplex crystals hold the melting points higher by 50 °C than homocrystals, nevertheless, stereocomplex crystals are commonly harvested in the low and moderate molecular weights of racemic blends due to their higher supercooling than homocrystals, not yet in the high molecular weight blends common for the commercial products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular simulations have demonstrated that under the same thermodynamic circumstances homocrystals grow faster than stereocomplex crystals, 4 but strain-induced crystallization enhances the preference of primary nucleation of stereocomplex crystals. 5 If the chain lengths are too small to make chain folding, intermolecular crystal nucleation becomes dominant and benefits stereocomplex crystals. 6 In practice, stereocomplex crystals hold the melting points higher by 50 °C than homocrystals, nevertheless, stereocomplex crystals are commonly harvested in the low and moderate molecular weights of racemic blends due to their higher supercooling than homocrystals, not yet in the high molecular weight blends common for the commercial products.…”
Section: Introductionmentioning
confidence: 99%
“…Another evidence for competition is the polymorphic crystallization of stereocomplex and homocrystals in racemic poly­(lactic acid) (PLA) blends, since intramolecular crystal nucleation is favored more by homocrystals of the same species than by stereocomplex crystals of alternatingly packed enantiomeric polymers. Molecular simulations have demonstrated that under the same thermodynamic circumstances homocrystals grow faster than stereocomplex crystals, but strain-induced crystallization enhances the preference of primary nucleation of stereocomplex crystals . If the chain lengths are too small to make chain folding, intermolecular crystal nucleation becomes dominant and benefits stereocomplex crystals .…”
Section: Introductionmentioning
confidence: 99%
“…Monte Carlo has also been used to study the kinetics and morphology of polymers undergoing crystallization under an applied 3-d flow [131], or strain-enhanced stereo-complex polymer crystallization [132]. In another study [133], the method was extended to binary blends of symmetric crystallizable polymers in which the authors enhanced (separately) the driving forces leading to polymer-uniform and polymer-staggered crystals.…”
Section: Polymer Crystallizationmentioning
confidence: 99%
“…The same simulation technique was used by Gu et al who studied the effects of nanoparticles on polymer crystallization in polymer solutions, focusing on filler dimension and size 26 . Guan et al performed dynamic Monte Carlo simulations to investigate strain‐induced polymer crystallization 27 . Recently, Verho et al studied the crystal growth of PE by molecular dynamics (MD) simulations 28 .…”
Section: Previous Work On Crystallizationmentioning
confidence: 99%